2019
DOI: 10.1159/000496283
|View full text |Cite
|
Sign up to set email alerts
|

Coil Extrusion into the Naso- and Oropharynx Ten Years after Internal Carotid Artery Pseudoaneurysm Embolization: A Case Report

Abstract: Coil migration and extrusion outside the cranial compartment after embolization of cerebral aneurysms represents a very rare complication of the endovascular procedures and few cases are reported in the literature. Instability of the vascular malformation wall and the resolution of the intramural hematoma, especially in pseudoaneurysm, might generate extravascular migration of the coils in the first months after embolization. However, to the best of our knowledge, an extrusion of coil 10 years after embolizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Conservative measures in cases such as these fail to address the worrisome infection risk and prophylactic anti-staphylococcal antibiotics are reasonable in the pre-operative and immediate post-operative period. Additional monitoring for prosthetic colonization and failure is likely warranted with one case report regularly following up until 6 months [5]. As endovascular coiling becomes more and more common, only time will tell if the incidence of coil erosion into the aerodigestive tract will increase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative measures in cases such as these fail to address the worrisome infection risk and prophylactic anti-staphylococcal antibiotics are reasonable in the pre-operative and immediate post-operative period. Additional monitoring for prosthetic colonization and failure is likely warranted with one case report regularly following up until 6 months [5]. As endovascular coiling becomes more and more common, only time will tell if the incidence of coil erosion into the aerodigestive tract will increase.…”
Section: Resultsmentioning
confidence: 99%
“…Several cases (Table 1) [3,4] have been reported in the literature following endovascular coiling of a traumatic pseudoaneurysm presenting within 6 weeks of coiling. Others have reported this as a late complication 10 years after coiling [5].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Coil extrusion into the nostril and oropharynx up to 26 months after neurointerventional therapy was reported in two cases (Struffert et al 2009). Nasi et al (2019) reported on a case in which coil extrusion had actually happened 10 years after the treatment was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported iatrogenic perforation of the aneurysmal wall during coiling (Aoun et al 2013) or the force of blood flow compressing the coils against the aneurysmal dome resulting in coil extrusion either through an already vulnerable site or by creating a new tear in the aneurysm wall (Wilseck et al 2018). The mechanics and process described above usually take time and reflect the fact that the extrusion is reported from several months to years after the endovascular coiling procedure (Nasi et al 2019). Extruded including axial T1WI (a), axial T2WI (b), and sagittal T2WI (c) showed a modification in the signal intensity of the thrombus.…”
Section: Discussionmentioning
confidence: 99%